A Similar Secretome Disturbance as a Hallmark of Non-pathogenic Botrytis cinerea ATMT-Mutants? - de Vallée, Amélie; Bally, Pascal; Bruel, Christophe; Chandat, Lucie; Choquer, Mathias; Dieryckx, Cindy; Dupuy, Jean William; Kaiser, Sophie; Latorse, Marie-Pascale; Loisel, Elise; Mey, Géraldine; Morgant, Guillaume; et al. (Frontiers in Microbiology, 2019)
The grey mould fungus Botrytis cinerea is a necrotrophic pathogen able to infect hundreds of host plants, including high-value crops such as grapevine, strawberry and tomato. In order to decipher its infectious strategy, a library of 2,500 mutants was generated by random insertional mutagenesis using Agrobacterium tumefaciens-mediated transformation (ATMT). Twelve mutants exhibiting total loss of virulence towards different host plants were chosen for detailed analyses. Their molecular characterization revealed a single T-DNA insertions in different loci. Using a proteomics approach, the secretome of four of these strains was compared to that of the parental strain and a common profile of reduced lytic enzymes was recorded. Significant variations in this profile, notably deficiencies in the secretion of proteases and hemicellulases, were observed and validated by biochemical tests. They were also a hallmark of the remaining eight nonpathogenic strains, suggesting the importance of these secreted proteins in the infection process. In the twelve nonpathogenic mutants, the differentiation of infection cushions was also impaired, suggesting a link between the penetration structures and the secretion of proteins involved in the virulence of the pathogen.